The triumph of Dionysos : convivial processions, from antiquity to the present day - Boardman, John, 1927- (Archaeopress, 2014)
Dionysos carried the blessing of wine to the whole world, and his triumphant return from India became a popular subject for the arts of Greece and Rome in many media. It became associated with Alexander the Great's comparable victories and later served as a message of immortality for any mortal prince. The iconography survived the ancient world into Renaissance and neo-Classical arts, and may even have contributed to the practices of modern circus parades with their wild animals, maenad-snake-charmers and clown-satyrs: an unusual, indeed unique, survival.